Study protocol: haemostatic efficacy and safety of preemptive antifibrinolysis with multidose intravenous tranexamic acid in elderly hip fracture patients: design of a prospective randomised controlled trial - Wei Huang; Jiacheng Liu; Xi Liang; Junyi Liao; Yiting Lei; Ning Hu (BMJ Open)
Introduction Hip fracture surgery is often associated with substantial blood loss and a high allogeneic blood transfusion (ABT) rate. Preoperative hidden blood loss (HBL) has been observed clinically but there is little evidence for the efficacy of tranexamic acid (TXA) in controlling preoperative HBL. We designed a randomised controlled trial to evaluate the efficacy of preemptive antifibrinolysis with multidose intravenous TXA (IV-TXA) in reducing preoperative HBL in elderly patients with hip fractures.Methods and analysis This is a prospective, randomised, placebo-controlled clinical trial. Patients older than 65 years diagnosed with primary unilateral femoral neck fracture or intertrochanteric fracture will be randomly assigned to group A (receiving 100 mL of intravenous normal saline every 12 hours preoperatively and 1.5 g of IV-TXA every 12 hours postoperatively for 3 days) or group B (receiving 1.5 g of IV-TXA every 12 hours preoperatively and 1.5 g of IV-TXA every 12 hours postoperatively for 3 days). The primary outcomes will be the hidden blood loss, haemoglobin decrease and ABT rate. The secondary outcomes include the levels of inflammatory factors (such as C reactive protein) and coagulation and fibrinolysis parameters (such as D-dimer). Other outcomes such as injury time, length of stay and hospitalisation expenses will also be compared between groups.Ethics and dissemination This study has been approved by the Ethics Committee of the First Affiliated Hospital of Chongqing Medical University. The findings of the study will be disseminated through peer-reviewed journals and conference presentations.Trial registration number ChiCTR2100045960.